2018
DOI: 10.1177/0959683618798131
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental changes during the last 3000 years in Lake Cari-Laufquen (Northern Patagonia, Argentina), inferred from ostracod paleoecology, petrophysical, sedimentological and geochemical data

Abstract: South American paleoreconstructions are of global interest because it is the only landmass extending from the tropics to the southern high latitudes and intersecting the entire southern westerly wind belt. In this context, endorheic environments, as Lake Cari-Laufquen Grande (LCLG; 41º35'S, 69º25'W) are excellent sites for paleoenvironmental studies, since they react rapidly to changes in the precipitation/evaporation ratio. In this study, the limnological conditions prevailing during the last 3000 years have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The presence of microfossils is very low to absent. This has been previously observed by Bradbury et al (); Coviaga et al (); Cusminsky et al (); Schwalb et al (); Whatley and Cusminsky () who all show a lack of well‐preserved diatoms and a relative paucity of ostracod assemblages. Pacton et al () in their study of modern microbial mats further observed dissolution patterns in diatom frustules.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The presence of microfossils is very low to absent. This has been previously observed by Bradbury et al (); Coviaga et al (); Cusminsky et al (); Schwalb et al (); Whatley and Cusminsky () who all show a lack of well‐preserved diatoms and a relative paucity of ostracod assemblages. Pacton et al () in their study of modern microbial mats further observed dissolution patterns in diatom frustules.…”
Section: Discussionsupporting
confidence: 79%
“…These records show a relatively low abundance of diatoms and a larger abundance and diversity of ostracods with Limnocythere rionegroenis as the dominant species, suggesting a turbid and possible saline lake. Several phases of increasing diversity in ostracod species indicate a probable decline in lake salinity and a higher lake level (Bradbury et al, ; Coviaga et al, ; Cusminsky et al, ). Unfortunately, these records are younger than the existing ages for the Maquinchao microbialites (Figure and Cartwright et al, ) or have uncertain ages (Whatley & Cusminsky, ) preventing a direct comparison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations